Evolution of Microporosities in Wide‐Thick Continuous Casting Slab during Heavy Reduction Process. Issue 7 (20th May 2022) - Zhang, Jinyuan; Wu, Chenhui; Ji, Cheng; Chen, Yi; Zhu, Miaoyong
Abstract : Heavy reduction (HR) is an effective process that can significantly minimize the internal porosity and other internal defects in continuous casting steel. Herein, samples taken from different wide‐thick slab positions are examined by scanning acoustic microscopy and 3D reconstructed. The morphology and distribution of microporosities <1 mm in size in the wide‐thick slab are revealed. The microporosities are mainly distributed in a stripping zone symmetric about the centerline within a 1/3‐slab thickness, and most have a considerably obvious long‐ and short‐axis tendency, which can be approximated as ellipsoids. The microporosity evolution in the wide‐thick slab during HR at the solidification end is numerically investigated with a 3D thermal–mechanical coupled model. The microporosity evolution in an aggregated distribution region during HR is little influenced by the surrounding microporosities. With increasing slab centerline‐microporosity distance, the microporosity minimization effect of HR becomes poor. When the axial ratio (long axis/short axis) is 1.43, the microporosity closure is the largest, and the porosity closure is the highest when the long axis is perpendicular to the reduction direction. When the total segment reduction is constant, the reduction mode with gradually decreasing reduction results in the highest total porosity closure and minimum reduction force. Abstract : The morphology and distribution of microporosities in the wide‐thick slab are revealed by scanning acoustic microscopy and 3D reconstructed technology. Meanwhile, the evolution of different kinds of porosity under heavy reduction is studied. The microporosities are mainly distributed in a stripping zone symmetric about the centerline within a 1/3‐slab thickness, and most can be approximated as ellipsoids.